Efficacy and Safety of Letrozole in Improving Semen Parameters of Subfertile Men with Moderate-to-Severe Oligoasthenoteratozoospermia: A Placebo-controlled Randomised Trial - Pallavi Ullur; N. S. Kubera; Soliappappan Manikandan; Nivedita Nanda; Sujatha Venkatraman; Anusuya Ram (Journal of Human Reproductive Sciences)
Background: Currently lack of consensus regarding the medical treatment of men with Oligoasthenoteratozoospermia (OATS). Letrozole is an aromatase inhibitor and may improve semen quality by stimulating hormone synthesis and spermatogenesis. There is lack of evidence on the efficacy and safety of letrozole as therapy for male infertility. Aim: To study the efficacy of letrozole in improving semen parameters, hormonal profile of participants with moderate-to-severe OATS and its side effects. Settings and Design: Randomised double-blinded placebo-controlled trials conducted in a tertiary care centre conducted between August 2021 and July 2023. Men with abnormal semen analysis reports between the age group of 21 and 45 years with moderate-to-severe OATS visiting the male infertility clinic were enrolled. Materials and Methods: Fifty-four men were randomised into two groups. Twenty-eight men in A (intervention group) received letrozole, and 24 men in Group B (control group) received a placebo after written informed consent. After 3 months, semen analysis and hormonal parameters were studied. Statistical Analysis Used: Data analysis was performed using SPSS version 19 (IBM). Associations between categorical variables in two groups were analysed using the Chi-square test or Fisher’s exact test. Continuous variables were compared using the Mann–Whitney test, and independent Students’ t-test and pre- and post-treatment comparisons of continuous variables were assessed using a paired t-test or Wilcoxon signed-rank test. Results: Total sperm count increased by 4.4 (2.8, 8.8) million per ejaculate, sperm concentration by 3.2 (1, 4.4) million/mL and progressive motility by 5.8 ± 7.3% compared to the placebo group, which was statistically significant (P = 0.001). The use of letrozole had minor side effects like headache and nausea. Letrozole use in men with OATS showed a significant improvement in follicle-stimulating hormone by 6.8 ± 5.5 mIU/mL, luteinising hormone by 6.3 ± 3.3 IU/L, testosterone by 193.3 ± 130 ng/dL, with P value of 0.001 and significant fall in oestradiol by 17.6 ± 7.9 pg/mL overall improving T/E ratio by 18.4 ± 8.8. Conclusion: Letrozole use may result in improving semen parameters in men with moderate-to-severe OATS. However, these findings need to be validated in larger trials.